Selection Of The Best Employees Using Analytical Hierarchy Process at PT. Gotrans Logsitics International Semarang Branch - Bachtiar Dwi Hari Putranto; Dedy Kurniadi; Asih Widiharini (Journal of Applied Science and Technology, 2021)
One form of appreciation that a company gives to employees is the selection of one or several employees to be the best employees, usually companies implement this program for the benefit of their respective companies. This program is also carried out by PT. Gotrans Logistics International Semarang branch to motivate the development of the quality of human resources to compete in a healthy manner which indirectly also has a good impact on the company. This best employee selection program will take a long time and the results are inaccurate if not assisted by a decision support system, therefore a decision support system is needed to get the expected results. Selection will be carried out by determining the weight of the desired criteria and then ranking the employees. With the creation of a decision support system using the Analytical Hierarchy Process (AHP) method, it can provide a solution in performing calculations and minimizing the time used in the selection.